Numerical and experimental study of initiation of cracking of UHPFRC by means of Brazilian tests. (April 2022) - Sanz, Beatriz; Planas, Jaime; Rey-de-Pedraza, Víctor; Sancho, Rafael; Sancho, José M.; Gálvez, Francisco
Abstract: An experimental and numerical study is presented in this work to analyse the applicability of the Brazilian test to determine the tensile strength of ultra-high performance fibre-reinforced concrete (UHPFRC), interpreted as the stress at which, in pure tension, crack initiates and softening begins. From dimensionless finite element simulations using a generalised cohesive crack model and elements with an embedded adaptable crack, it has been assessed that a local maximum in stress occurs in the Brazilian test which is very close to the tensile strength. This local maximum can be detected from the measurement of the relative displacement of two points symmetric with respect to the diametral loading plane. An experimental device has been designed to materialise that measurement by means of an extensometer supported by extensions glued at the bases of the cylindric specimen. Experiments have been conducted for specimens with three contents of fibres and for the base material under load control, and the experimental curves display a neat pop-in, i.e., an abrupt increase of the measured displacement under almost constant load, which must coincide with the local maximum determined in the numerical simulation and allows the corresponding stress to be determined with enough accuracy, thus, demonstrating the validity of the Brazilian test if sufficiently instrumented to determine the tensile strength of UHPFRC. Highlights: Application of Brazilian tests to obtain the tensile strength of UHPFRC is studied. Simulations using a generalised cohesive model and embedded crack are performed. A local peak of stress appears close to the tensile strength at crack initiation. Brazilian tests adequately instrumented allow detection of the local peak. Results obtained for several contents of fibres demonstrate the validity of the test.